(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Logistics industry provides significant macro contributions to national economy by creating employment, and creating national income and foreign investment influx. On the micro scale, logistics industry is a key industry in increasing the competitive power of corporations.